Self-Reported History of Seizure, Baseline Neurocognitive Performance, and Symptoms Reported in High School Athletes. (26th July 2019) - Datoc, A; Lashley, L
Abstract: Purpose: To examine whether a self-reported history of seizure is associated with differences in baseline neurocognitive performance and total reported symptoms. Methods: Data was derived from a de-identified Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) database of high school athletes in Florida. After inclusion and exclusion criteria were applied, athletes were separated into groups dependent on self-reported history of seizure. 260 athletes (Mage=15.49, SD=1.26; 57.1% male) reported a history of seizure, and 260 athletes were randomly selected from those with no such history (Mage=15.64, SD=1.22; 61.1% male). Results: ANOVA (alpha=.05) revealed significant differences between groups on the visual memory composite (F[1, 559]=4.915, p=.027) and total symptom score (F[1, 559]=28.596, p<.001) at baseline. Athletes with a self-reported history of seizure performed significantly worse than athletes without on visual memory and reported significantly higher total symptom scores. No significant between-group differences were found on the other composites of ImPACT. Conclusion: The association between seizure history and decreased neurocognitive performance has been documented in the neuropsychological literature, and may be explained by differences at a microstructural level such as differences in white matter integrity (Yassine et al., 2018). While these microstructural differences have implications on cognitive functioning and symptomatology, the present study surprisingly found comparable scores between athletes with a history of seizure and those without. Previous researchers published similar findings; however, differences were observed on the visual-motor speed composite of ImPACT (Zalneraitis et al., 2017). The inconsistencies and small effect sizes in the present literature highlight the need for investigators to determine the clinical significance of these results in concussion evaluations.